Students of Special Educational Disciplines – Issue of Socializing and Educating People With Hearing Impairment - Svecova, Veronika (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The contribution presents results of research which is focused on issue of socialization of people with hearing impairment. It is focused on the point of view of students of special education major. Research included 127 students of special education major who studied full time or distance study form. The questionnaire was used as research method and it included 28 opened and closed questions. The author also used Likert scale. Results showed that students of special education major prefer education of pupils with hearing impairment in the school for pupils with hearing impairment. Hearing impairment influences all areas of life - education, employment, relationships with peers, free time activities and partner relationships.